Pengembangan LAPD Berbasis Project Based Learning dengan Strategi Mind Mapping untuk Meningkatkan Keterampilan Berpikir Kreatif Peserta Didik pada Materi Kimia Hijau - Mulyasari, Yuyun; Mitarlis, Mitarlis (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2025)
Learning outcome at 21st century requires creative thinking skills with students centered learning experience. Project based learning model with mind mapping strategies can be used to encourage activeness and improve creative thinking skills. Supporting learnig media is needed, such as LAPD project based learning with mind mapping strategy. The purpose of this study is to describe the feasibility of LAPD project based learning with a mind mapping strategy to improve creative thinking skills developed in terms of validity, practicality, and effectiveness. The type of research used is Research and Development (R&D) with the 4D model development method. The results of this study indicate that the developed LAPD is valid, with a mode of 4 categories of validity and a mode of 5 categories of high validity. The developed LAPD was deemed practical based on observations of learning implementation, which obtained a mode of 4 and 5, indicating good and very good, respectively. Additionally, through observations of student activities, the average relevant activity was 96.57% and irrelevant activity was 3.43%. Furthermore, through student responses to the learning implementation, 90% were positive, and 93% were positive toward the LAPD. The LAPD was also found to be effective in enhancing creative thinking skills in the green chemistry pretest and posttest and mind mapping test, as evidenced by the paired t-test results for both tests yielding <0.05, and the N-gain values for the mind mapping test at 0.70 and for the green chemistry material at 0.77, both in the very high category. Thus, the developed LAPD is suitable for use in green chemistry learning and capable of enhancing creative thinking skills.